Confined mass transfer mechanism and preparation strategies of separation membranes: A review - Yongqiang Guo; Hongbin Li; Chao Liu (Materials & Design, 2023)
The membrane technology has attracted increasing attention in the field of separation and desalination due to its high efficiency, energy saving, environmental protection, and other advantages. However, related mass transfer theories especially under confined conditions (such as reverse osmosis and nanofiltration) lack the understanding of common mass transfer mechanisms and control methods, thereby seriously restricting the design and development of related membrane materials. This article reviews the research progress of separation membranes with confined mass transfer effects in recent years and analyzes the challenges faced by classical mass transfer models under confined mass transfer conditions. The confined mass transfer mechanism, influencing factors, construction methods, and types of preparation materials are summarized. Furthermore, the development of confined mass transfer separation membranes and the problems to be solved are prospected. Nanomaterial-modified membranes with confined mass transfer function are most likely to break through the trade-off effect of high flux and high selectivity. The confined mass transfer mechanism and preparation strategies of separation membranes are rarely reviewed. Hence, this review can provide guidance for new entrants and existing researchers in the field of membrane separation and has certain reference value for the development of confined mass transfer membranes in the future.